Building Resilience in a Federal System: A Performance Audit of Nepal’s Progress Towards SDG Target on National Public Health Emergency Preparedness - Pandey, Namuna (Journal of Multidisciplinary Research Advancements, 2025)
Sustainable Development Goal (SDG) Target 3.d focuses on measuring a country’s strengthening of self-contained early warning, risk assessment and management, and health risk reduction through core International Health Regulations (IHR). IHR is an instrument of international law, adopted pursuant to Article 21 of the World Health Organisation (WHO) Constitution, and is legally binding on 196 States Parties, including all 194 Member States of WHO. This paper examines how Nepal endeavours to achieve this target in the context of the country’s transition to a federal governance system. A performance audit was conducted, utilising data from secondary sources (2016 onwards), including government publications, reports from international agencies, and peer-reviewed academic articles. A specific case study on the response to COVID-19 was included. Analysis was conducted in accordance with the International Organisation of Supreme Audit Institutions (INTOSAI) guidelines for self-contained report evaluations, focusing on possible divergence and convergence, the Leave No One Behind (LNOB) principles, cross-domain considerations, and structural finance. Progress is undermined by a controlled information vacuum. Since the last IHR was issued in 2015, the country has been in a state of stagnation, albeit self-sustaining. Although the country has a constitutional basis for health, policy and implementation levels are characterised by widespread vertical and horizontal misunderstandings among federal, provincial, and local governments. The COVID-19 response relegated the issue of ‘proliferated temporary control mechanisms’ or missing rational command systems. Financial analysis showed what appeared to be “firefighting” models, which allocated declining investments to the core preparedness functions like epidemic control, which fell to 2% of the federal health budget in 2021/22, and spending for COVID-19 emergencies, which constituted 36% of the federal health budget in 2021/22. The overarching Target 3.d monitoring and evaluation mechanisms were weak and lacked specified operations for subnational units. The systemic governance and financing issues inherent to transition federalism, which are inescapable for Nepal, pose acute challenges to achieving SDG Target 3.d by 2030. Scaling the governance system while strengthening IHR financing and core systems, and monitoring discretion through proactive mechanisms, is imperative for the resilience of the National Public Health System.